Los roles de Gregoria Apasa en la rebelión altoperuana de 1781 - Nogueira, Patricia (2023)
By February 1781, several towns that secured the entrance to the city of La Paz from the valleys had risen against Spanish power under the command of a common Aymara Indian named Julián Apasa, who later took the name of Tupac Katari. Almost parallel to this movement, during the month of April, with the capture of Tupac Amaru II, Diego Cristóbal Tupac Amaru transferred the rebel camp to Azángaro. From that moment on, Amarus and Kataris began to share the rebel geography. This situation required them to establish negotiations and certain agreements, unavoidable when facing a common enemy. No one could lose sight of the fact that coordinated and joint actions would help hit the Spanish harder, obtaining a faster victory and one less onerous in terms of material resources and human lives. It was from those agreements onwards that Gregoria Apasa, Tupac Katari’s sister, played significant roles, both at the family level as well as at political, military and leadership levels.